RECENT PERIODICALS RELATING TO THEOLOGICAL STUDIES (The journal of theological studies, 1927)
RECENT PERIODICALS RELATING TO THEOLOGICAL STUDIES, The Journal of Theological Studies, Volume os-XXVIII, Issue July, 1 July 1927, Pages 447–448, https://doi.or